2018
DOI: 10.20849/ijsn.v3i3.525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breathing Exercises on Quality of Recovery Among Postoperative Patients

Abstract: Postoperative breathing exercises are widely important for patient to prevent postoperative respiratory complications. Breathing exercises had a highly positive effect on improving quality of recovery among post-operative patients. This study aimed to assess the effect of breathing exercises on quality of recovery among post-operative patients. Setting at Zagazig University Hospitals. Material and Method: a quasi-experimental (pre and posttest design). A purposive sample of total 258 study participants, 129 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The current trend of rapid transition in the healthcare system means that patients are discharged quickly and that the responsibility for postoperative recovery is largely transferred to patients and their families (Hussein & Taha, 2018). Recovery quality is an important indicator of the early postoperative health status of patients after anesthesia (Myles et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The current trend of rapid transition in the healthcare system means that patients are discharged quickly and that the responsibility for postoperative recovery is largely transferred to patients and their families (Hussein & Taha, 2018). Recovery quality is an important indicator of the early postoperative health status of patients after anesthesia (Myles et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Breathing exercises, the first step of relaxation, which is a nonpharmacological method, increase the release of endorphins by distracting the patient’s attention from pain and reducing pain (Çapık et al, 2016; Mert & Göktaş, 2018). Hussein and Taha (2018) conducted a study with 258 patients who had undergone surgery and found that the pain level of the patients in the group doing breathing exercises decreased. Doing breathing exercises through a planned and regular animation program after surgery can increase the amount of O 2 carried to the tissues, accelerate tissue healing, and contribute to a reduction of pain in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2021) found that postoperative pulmonary complications were lower in an animation education group (Li et al, 2021). Hussein and Taha (2018) determined that dyspnea and other pulmonary complications were less common in the patient group who did breathing exercises. Another study found that deep breathing exercises improved respiratory functions and prevented postoperative pulmonary complications (Tripathi & Sharma, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-operative education intervention effectively post-operative oxygenation among other surgery such as orthopaedic surgery. According to Hussein and Taha, (2018), patients who practice deep breathing had a better quality of recovery in post-operative phase compared with those who do not practice. Therefore, the content of pre-operative education package should be informative and straightforward to ensure the effectiveness of the pre-operative education CABG surgery patient.…”
Section: Discussionmentioning
confidence: 99%